Nilai-nilai Pendidikan Islam dalam Film Animasi Nussa Episode Sholat Itu Wajib - Muhammad Shodiq Masrur; Asyhari Amri (LP2M STIT Palapa Nusantara, 2021)
The current era, with fertile technology that is increasingly developing, certainly has positive and negative sides. One of the phenomena that shows the negative side of development technologies such as Youtube, Instagram, Twitter and Facebook is that many cildren use media gadgets as playmates, so that the child is not controlled is choosing content that is popular in cyberspace, as a reseult the child will further away from values religion, humanitarian values, values justice and moral values. In this article, the researcher describes the prevention of moral decadence for the younger generation, so it is necessary to increase the role of education, especially the role of parents in selecting entertaiment content that contains moral values for children. These efforts are made to prepare the next generation who have knowledge, faith and good character. The writing of this article uses qualitative research with descriptive analysis. The writer in this article uses Roland Barthes’ semiotic analysis model known as “two order of signification”, namely by looking for the denotative meaning the connotation of each scene. From using this method the researcher foumd that the animated film Nussa and Rarra, the episode of prayer must contain values from the concept of Islamic teachings, namely Akidah, Sharia and Moral. If parents are able to nurture and guide by choosing content that educated and implements in life, it is hoped that the child will become a person with character according to the expectation of the nation and religion. Islamic